Pengenalan Penggunaan Aplikasi “ACOV19” Sebagai Activity Tracking dan Media Literasi Digital di Kelurahan Tanjungmas - Edi Jaya Kusuma; Sri Handayani; Ririn Nurmandhani (LPPM UNIVERSITAS DIAN NUSWANTORO, 2022)
Dian Nuswantoro University in particular the Faculty of Health has developed an application whose main focus is activity tracking and digital media literacy for users named ACOV19. The use of activity tracking applications in the pandemic era is expected to be able to ease the work of the government and read the data transaction process. However, some people still do not understand the importance of this. In addition, socializing the use of applications that are still less popular makes these applications less popular. The purpose of this service is to provide an understanding of literacy and the use of the